Herpes simplex virus downregulation of secretory leukocyte protease inhibitor enhances human papillomavirus type 16 infection - Skeate, Joseph G. (J Gen Virol, 2016)
Herpes simplex virus (HSV) was originally implicated in the aetiology of cervical cancer, and although high-risk human papillomavirus (HPV) is now the accepted causative agent, the epidemiological link between HSV and HPV-associated cancers persists. The annexin A2 heterotetramer (A2t) has been shown to mediate infectious HPV type 16 (HPV16) uptake by human keratinocytes, and secretory leukocyte protease inhibitor (SLPI), an endogenous A2t ligand, inhibits HPV16 uptake and infection. Interestingly, HSV infection induces a sustained downregulation of SLPI in epithelial cells, which we hypothesized promotes HPV16 infection through A2t. Here, we show that in vitro infection of human keratinocytes with HSV-1 or HSV-2, but not with an HSV-1 ICP4 deletion mutant that does not downregulate SLPI, leads to a >70 % reduction of SLPI mRNA and a >60 % decrease in secreted SLPI protein. Consequently, we observed a significant increase in the uptake of HPV16 virus-like particles and gene transduction by HPV16 pseudovirions (two- and 2.5-fold, respectively) in HSV-1- and HSV-2-infected human keratinocyte cell cultures compared with uninfected cells, whereas exogenously added SLPI reversed this effect. Using a SiMPull (single-molecule pulldown) assay, we demonstrated that endogenously secreted SLPI interacts with A2t on epithelial cells in an autocrine/paracrine manner. These results suggested that ongoing HSV infection and resultant downregulation of local levels of SLPI may impart a greater susceptibility for keratinocytes to HPV16 infection through the host cell receptor A2t, providing a mechanism that may, in part, provide an explanation for the aetiological link between HSV and HPV-associated cancers.